Altered electrical properties with controlled copper doping in ZnO nanoparticles infers their cytotoxicity in macrophages by ROS induction and apoptosis. (5th January 2019) - Das, Bikram Keshari; Verma, Suresh K.; Das, Tanushree; Panda, Pritam Kumar; Parashar, Kajal; Suar, Mrutyunjay; Parashar, S.K.S.
Abstract: The present study reports the regulation of cytotoxicity of Cu doped ZnO nanoparticles in macrophages (RAW 264.7) due to altered physiochemical properties changes like electrical properties by controlled doping of Cu in ZnO. Cu-doped ZnO nanoparticles were prepared by High Energy Ball Milling technique (HEBM) and formed single phase Zn1-x Cux O (x = 0.0, 0.01, 0.02, 0.03) were called as pure ZnO, Cu1%, 2%, 3% respectively. Hexagonal wurtzite structure with size range of 22–26 nm was verified. FE-SEM with EDX analysis indicated the Cu doping effect on the surface morphology of ZnO. Zeta potential of Zn1-x Cux O was found to be elevated with increase in doping percentage of Cu (−36.6 mV to +18.2 mV). Dielectric constant was found to be decreased with increasing doping percentage. Increase in doping percentage enhanced cytotoxicity of Zn1-x Cux O in macrophages with LC50 of 62 μg/ml, 51 μg/ml, 40 μg/ml, 32 μg/ml. Granularity change of macrophages suggested doping influenced cellular uptake as consequence of zeta potential and dielectric properties changes. 3% Cu doped ZnO shown a higher ROS signal and apoptosis than 2% and 1% Cu doping with exhibition of ROS scavenging nature leading to apoptosis of prepared Cu doped ZnO nanoparticles. Our findings revealed mechanism of cytotoxicity of Zn1-x Cux O as a consequence of alteration in electric properties eliciting ROS scavenging leading to higher apoptosis with increasing doping percentage of Cu in ZnO. Highlights: Cu doped ZnO nanoparticles were prepared by HEBM technique. Zeta potential and Dielectric constant were increased and decreased respectively with increase in doping percentage of Cu. Increase in Cu doping percentage increases the cytotoxicity of ZnO. Cytotoxicity is mediated by ROS quenching and Apoptosis.